Enhanced Crop Discrimination and Monitoring Using Compact-Polarimetric SAR Signature Analysis From RADARSAT Constellation Mission - Hamid Jafarzadeh; Abhinav Verma; Masoud Mahdianpari; Avik Bhattacharya; Saeid Homayouni (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
With the rapid advancements in SAR systems aiming for operational capabilities, crop characterization using compact-polarimetric synthetic aperture radar (CP-SAR) data has gained considerable attention. This study thoroughly assesses the potential usefulness of C-band SAR data in CP mode using the RADARSAT Constellation Mission (RCM) for crop monitoring. The research unfolds across two separate phases: 1) Extensive crop scattering characterization and 2) Crop classification. In the first part, we introduce three descriptors: compact-polarimetric SAR signature (CPS), differential CPS (DCPS), and the geodesic distance (GD) between signatures, to characterize the scattering pattern of four crop types: soybean, hay, corn, and cereal. We, then, derive the $μ$ parameter and employ it in the $μ -χ$ decomposition method. Time-series investigation of the proposed descriptors and the three power components: $P_{s}$ , $P_{d}$ , and $P_{v}$ provide valuable insights into the scattering responses exhibited by crops, facilitating a robust assessment and tracking of their growing cycle, thus, enabling the potential for improving crop discrimination. In the second part, we employ the $μ -χ$ and $m-χ$ decompositions and wave descriptors to extract a stack of CP features for crop mapping. Combining diverse feature types and leveraging single- and multi-date RCM images, classification experiments yield an optimal classification map with an overall accuracy of 89.71%, particularly when utilizing features extracted from multi-date datasets. This study illustrates a substantial effort in crop classification, underscoring the potential of the RCM CP-SAR mission. Furthermore, our findings emphasize the potential of CP-SAR data from the RCM mission in contributing to precision agriculture and sustainable crop management practices.